2021
DOI: 10.3390/molecules26206098
|View full text |Cite
|
Sign up to set email alerts
|

Aurones and Flavonols from Coreopsis lanceolata L. Flowers and Their Anti-Oxidant, Pro-Inflammatory Inhibition Effects, and Recovery Effects on Alloxan-Induced Pancreatic Islets in Zebrafish

Abstract: (1) Background: Many flavonoids have been reported to exhibit pharmacological activity; a preparatory study confirmed that Coreopsis lanceolata flowers (CLFs) contained high flavonoid structure content; (2) Methods: CLFs were extracted in aqueous methanol (MeOH:H2O = 4:1) and fractionated into acetic ester (EtOAc), normal butanol (n-BuOH), and H2O fractions. Repeated column chromatographies for two fractions led to the isolation of two aurones and two flavonols; (3) Results: Four flavonoids were identified bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
(56 reference statements)
0
3
0
2
Order By: Relevance
“…Extracts, solvent fractions (EtOAc, n -BuOH), and isolated phenylalkyl glucosides 1 – 6 from B. arborea flowers were evaluated for protective activity against the pancreatic islets of zebrafish larvae damaged by alloxan. The larvae treated with alloxan were used to model type 1 diabetes due to their physiological similarities to mammals [ 21 , 22 ]. Alloxan is a diabetogenic chemical that has been reported to decrease β -cell mass in pancreatic islets [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extracts, solvent fractions (EtOAc, n -BuOH), and isolated phenylalkyl glucosides 1 – 6 from B. arborea flowers were evaluated for protective activity against the pancreatic islets of zebrafish larvae damaged by alloxan. The larvae treated with alloxan were used to model type 1 diabetes due to their physiological similarities to mammals [ 21 , 22 ]. Alloxan is a diabetogenic chemical that has been reported to decrease β -cell mass in pancreatic islets [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that AST exerted anti-inflammatory effects by antagonizing the increase of nitric oxide (NO), tumor necrosis factor-α (TNF-α), PGE2, interleukin (IL)-1β, IL-6, IL-12, IL-13, IL-18, and leukotriene B4 (LTB4) in the lipopolysaccharide (LPS) and interferonγ (IFN-γ)-stimulated RAW264.7 cells [31][32][33][34]. In LPS-induced mouse macrophage J774A.1 cells, AST significantly decreased the pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and chemokine macrophage inflammatory protein-1α (MIP-1α), as well as the gene expression of macrophage chemoattractant protein-1 (MCP-1).…”
Section: The Effect Of Astragalin On Macrophage Inflammation-related ...mentioning
confidence: 99%
“…Nghiên cứu sự thay đổi kích thước của tiểu đảo tụy sau khi được xử lý với alloxan, hợp chất auron 35, 36 và chứng dương glimepirid (một loại thuốc chống đái tháo đường tuýp II) thu được kết quả như sau: alloxan làm giảm kích thước tiểu đảo tụy tương đối mạnh (47,8%) nhưng khi tiểu đảo tụy bị tổn thương được xử lý với auron 35, 36 thì sẽ khôi phục kích thước của tiểu đảo tụy với phần trăm lần lượt khoảng 98,7% và 89,8%. Trong đó, auron 35 gây ra sự khôi phục tương đương so với chứng dương glimepirid [50]. Hình 15.…”
Section: Hình 10 Cấu Trúc Những Auron Có Tiềm Năng Kháng Ung Thư Hoạt...unclassified